The Effect of Physical Activity on Quality of Life and Emotional State of Students - Ciftci, Betul; Gür, Ozan; Özüberk, Burcu (Baiman Bauntung Batuah Center, 2024)
Physiotherapists and nurses are crucial members of the healthcare team, and members of the healthcare team should be aware of the importance of physical activity to promote it in society. This study aimed to assess the effects of physical activity levels on the quality of life and emotional state of first-year nursing, physiotherapy, and rehabilitation students. One hundred six first-year nursing, physiotherapy, and rehabilitation students participated in the study. Socio-demographic characteristics were appraised. The Beck Depression Inventory (BDI) and the Nottingham Health Profile (NHP), Pittsburgh Sleep Quality Index (PSQI) and the International Physical Activity Questionnaire Short Form (IPAQ-SF) were administered to all participants. The activity level of 51.9 % of all students was inactive. The mean values of NHP-sleep, NHP-SI, NHP-1, NHP-2, and BDI scores were higher in nursing students than in physiotherapy and rehabilitation students (p<0.05). According to the results of this study, physical activity among first-year nursing and physiotherapy and rehabilitation students is insufficient. More studies are needed about the reasons for insufficient physical activities in students and how to increase awareness of physical activity.